FORMATION OF WEAR-RESISTANT CHROMIUM CAST IRON CASTING INTO THE CHILL MOLD - E. I. Marukovich; V. M. Ilyushenko; P. Yu. Duvalov (Литьë и металлургия, 2013)
The analysis of thermal processes of formation of castings from wearproof chromic cast irons for replaceable details of centrifugal mills and crushers is carried out. Influence of protective and dividing coverings on intensity of heating of the chill mold is investigated.